The Drosophila melanogaster Levodopa-Induced Depression Model Exhibits Negative Geotaxis Deficits and Differential Gene Expression in Males and Females - Moulin, Thiago C.; Ferro, Federico; Hoyer, Angela; Cheung, Pierre; Williams, Michael J.; Schiöth, Helgi B. (Frontiers in Neuroscience, 2021)
More than 320 million people live with depression in the world, a disorder that severely limits psychosocial functioning and diminishes quality of life. The prevalence of major depression is almost two times higher in women than in men. However, the molecular mechanisms of its sex-specific pathophysiology are still poorly understood. Drosophila melanogaster is an established model for neurobiological research of depression-like states, as well as for the study of molecular and genetic sex differences in the brain. Here, we investigated sex-specific effects on forced-climbing locomotion (negative geotaxis) and gene expression of a fly model of depression-like phenotypes induced by levodopa administration, which was previously shown to impair normal food intake, mating frequency, and serotonin concentration. We observed that both males and females show deficits in the forced-climbing paradigm; however, modulated by distinct gene expression patterns after levodopa administration. Our results suggest that Drosophila models can be a valuable tool for identifying the molecular mechanisms underlying the difference of depressive disorder prevalence between men and women.